Economic Systems: Private Rights and Public Problems: The Global Economics of Intellectual Property in the 21st Century - Hu, Albert G. (Journal of Economic Literature, 2013)
Albert G. Hu of National University of Singapore reviews, “Private Rights and Public Problems: The Global Economics of Intellectual Property in the 21st Century” by Keith E. Maskus. The Econlit abstract of this book begins: “Presents an economic perspective on intellectual property rights and their relationship to global issues. Discusses the big stakes in selling knowledge; the big global upgrade—is it working?; global governance; regulating a stressed system; intellectual property rights and global policy challenges; and revitalizing a tired system. Maskus is Research Fellow at the Peterson Institute for International Economics, Professor of Economics and Associate Dean for Social Sciences at the University of Colorado at Boulder, a fellow at the Kiel Institute for World Economics, and an adjunct professor at the University of Adelaide.”